Deep eutectic solvents as cryoprotective agents for mammalian cells. Issue 24 (7th June 2022) - Bryant, Saffron J.; Awad, Miyah N.; Elbourne, Aaron; Christofferson, Andrew J.; Martin, Andrew V.; Meftahi, Nastaran; Drummond, Calum J.; Greaves, Tamar L.; Bryant, Gary
Abstract : A deep eutectic solvent is an effective cryoprotective agent for several human cell lines. Abstract : Cryopreservation has facilitated numerous breakthroughs including assisted reproductive technology, stem cell therapies, and species preservation. Successful cryopreservation requires the addition of cryoprotective agents to protect against freezing damage and dehydration. For decades, cryopreservation has largely relied on the same two primary agents: dimethylsulfoxide and glycerol. However, both of these are toxic which limits their use for cells destined for clinical applications. Furthermore, these two agents are ineffective for hundreds of cell types, and organ and tissue preservation has not been achieved. The research presented here shows that deep eutectic solvents can be used as cryoprotectants. Six deep eutectic solvents were explored for their cryoprotective capacity towards mammalian cells. The solvents were tested for their thermal properties, including glass transitions, toxicity, and permeability into mammalian cells. A deep eutectic solvent made from proline and glycerol was an effective cryoprotective agent for all four cell types tested, even with extended incubation prior to freezing. This deep eutectic solvent was more effective and less toxic than its individual components, highlighting the importance of multi-component systems. Cells were characterised post-thawing using atomic force microscopy and confocal microscopy. Molecular dynamics simulations support the biophysical parameters obtained by experimentation. This is one of the first times that this class of solvents has been systematically tested for cryopreservation of mammalian cells and as such this research opens the way for the development of potentially thousands of new cryoprotective agents that can be tailored to specific cell types. The demonstrated capacity of cells to be incubated with the deep eutectic solvent at 37 °C for hours prior to freezing without significant loss of viability is a major step toward the storage of organs and tissues.